Serious - Kaplan, James and McEnroe, John (London Little, Brown an Imprint of Time Warner Books, 2002)
Mild shelf wear to cover, reflected in price. An inspiring, enthralling, candid, honest and totally readable sports book about one of the most loved & hated personalities in world sport. Either side of the fence will be totally riveted.
Include Illustrations.
English Biography.
Keywords: Tennis players -- United States -- McEnroe, John, 1959-